SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF IRON CYCLOHEXANEDICARBOXYLIC ACID AND EXAMINATION OF pH EFFECT ON EXTRACTION IN WATER AND ORGANIC PHASES - Nilgün Becenen; Gühergül Uluçam; Özlen Altun (Trakya University Journal of Natural Sciences, 2017)
In this study, iron cyclohexanedicarboxylic acid was synthesized under refluxing conditions. The structural characterization of the complex was performed by using physico-chemical and spectroscopic methods. The effect of pH on division constant (µ) and extraction percentages (% E) in water and organic phase was investigated with the extraction method. At the end of the experiment, most of the Fe2+ ions in the water phase at pH=7.5 passed into the organic phase. Above this pH, the extraction percentage decreased because of the transition from water phase to organic phase. Iron cyclohexanedicarboxylic acid was extracted with ether, petroleum ether, benzole and carbon tetrachloride from aqueous solution and microbial activities of the complex were studied. The activity data showed that iron cyclohexanedicarboxylic acid has an important antibacterial and antifungal activities.